STRATEGI BISNIS PT. PERIKANAN SAMODRA BESAR CABANG BENOA-BALI UNTUK MENCAPAI TARGET EKSPOR - RUSMINI, NYOMAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003, 2012)
This research aim to formulate business strstegy of PT Perikanan Samodra Besar of Bali-Benoa branch to achieve export targets. Choises of the research location use the purposive methods. The data analysis use Strengths, Weakness, Opportunities Threats (SWOT) methods, namely to analys the firm internal and external factors in framework to formulate axatly business strategy. SWOT analysis to result four combination of strategy i.e.: Strengths-Opportunity (SO) strategy is a strategy use strengths to utilize the opportunity, Strengths-Threats (ST) strategy is a strategy use strengths to overcome the threaths, Weakness Opportunity (WO) strategy is a strategy to minimize the weakness to utilize opportunity, and Weakness-Treaths (WT) strategy is a strategy to minimize the weakness and overcome the threaths. Based on the result analysis of the internal and external factors, PT. Perikanan Samodra Besar Benoa branch has the competitive advantage compared their main competitor in term business experience, export market share, available the facility completely and the famous of firm name. Yet, the corporation less advantage in product quality, product diversification and market segmetation. Strategy can be formulated to achieve the export target are: SO strategy i.e.: to increase volume export, selves product as well as buying other firm products, to increase the product though to add the fishing at the own ships and reevaluate the fishing numbers that succes to get the weight and kind of the good fishes. ST strategy i.e.: to keep the harmony relationships with employees and to expand the market. WO strategy i.e.: to inctrease the promotion through internet medium, product diversification with make the fillet product and implemented the Hazzard Analysis Critical Control Point (HACCP) plan namely to monitor and control sistematicaly as long as production process untill the end product so that can result the good quality products. WT strategy i.e.: to increase the services towards consumers and human resources training continously.
Keywords: Fisheries, Competitive, SWOT Methods, Business Strategy and Export Targets